1999
DOI: 10.1046/j.1471-4159.1999.0731422.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Glutathione Reductase from Bovine Brain, Generation of an Antiserum, and Immunocytochemical Localization of the Enzyme in Neural Cells

Abstract: Glutathione reductase (GR) is an essential enzyme for the glutathione-mediated detoxification of peroxides because it catalyzes the reduction of glutathione disulfide. GR was purified from bovine brain 5,000-fold with a specific activity of 145 U/mg of protein. The homogeneity of the enzyme was proven by sodium dodecyl sulfate -polyacrylamide gel electrophoresis and silver staining of the gel. The purified GR from bovine brain is a dimer of two subunits that have an apparent molecular mass of 55 kDa. The purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 50 publications
5
29
0
1
Order By: Relevance
“…The high specific activities of GPx and GR in microglial cultures are in accordance with the observations that immunoreactivity of GPx in brain slices is most prominent in microglia [Lindenau et al, 1998], and that in astroglia-rich primary cultures, microglial cells stain intensively for GSH and GR [Chatterjee et al, 1999;Gutterer et al, 1999].…”
Section: Discussionsupporting
confidence: 86%
“…The high specific activities of GPx and GR in microglial cultures are in accordance with the observations that immunoreactivity of GPx in brain slices is most prominent in microglia [Lindenau et al, 1998], and that in astroglia-rich primary cultures, microglial cells stain intensively for GSH and GR [Chatterjee et al, 1999;Gutterer et al, 1999].…”
Section: Discussionsupporting
confidence: 86%
“…The cultures were used for experiments at an age between 15 and 27 days. Immunocytochemical studies have shown that the astrocyterich cultures comprise more than 90% astrocytes and contain small fractions of oligodendroglial, ependymal, and microglial cells but no neurons (Löffler et al, 1986;Reinhart et al, 1990;Gutterer et al, 1999;Dang et al, 2009). …”
Section: Cell Culturesmentioning
confidence: 99%
“…Although the recycle system of GSSG, comprising GR and NADPH, is the predominant one, few studies have demonstrated the localization of the GR protein. It is present in tissues such as lung cancer cells [10] and brain cells [11,12].…”
Section: Introductionmentioning
confidence: 99%